Highly Efficient Direct Allylation of Oxindoles with Simple Allylic Alcohols Enabled by Palladium/Brønsted Acid Catalysis - Yang, Huameng; Zhou, Hui; Yin, Hongyu; Xia, Chungu; Jiang, Gaoxi (Synlett, 2014)
A highly efficient and practical direct allylic alkylation of oxindoles with simple allylic alcohols cocatalyzed by Pd(OAc)2/Ph3P and PhCO2H under mild conditions has been developed, which streamlines the installation of an all-carbon quaternary allylic center at the oxindole 3-position. Enantioselective allylic alkylation has also been realized with the product in almost quantitative yield and 17% enantiomeric excess. Mechanistically, ESI analysis indicates that a palladium(0) species and π-allyl-Pd(PPh3)2 cation were involved.
Keywords: oxindole; allylic alkylation; Brønsted acids; allylic alcohol; palladium